Family-based intervention for patients with type 2 diabetes via WeChat in China: protocol for a randomized controlled trial - Linqi Mao; Jun Lu; Qi Zhang; Yuxi Zhao; Gang Chen; Mei Sun; Fengshui Chang; Xiaohong Li (BMC Public Health, 2019)
Abstract Background China has the largest number of cases of diabetes with a high rate of uncontrolled blood sugar. Many studies show that family members’ involvement is related to better glycemic control. However, there is a significant problem with low participation of family members. The widespread use of WeChat provides an opportunity for family members to support their diabetic loved ones in their type 2 diabetes self-management practices. The main aim of this study is to examine the effectiveness of a family-based intervention via WeChat. Methods A parallel, two-group, randomized controlled trial will be conducted in the central urban area of Jiading district in Shanghai, China. A total of 222 type 2 diabetics will be randomly divided into an intervention group or a control group using a 1:1 ratio. Patients in the intervention group will receive the usual care, and their family will get education in diabetes control and the importance of family support by subscribing to the WeChat public account. Both the patients and the family members will be followed up at 12 months after the intervention commences. Data collection is scheduled at baseline, 6-months, and 12-months. Discussion Family involvement based on WeChat may generate ongoing support for type 2 diabetic patients and improve these patients’ health outcomes. A successful outcome of this study may also provide inspiration for other efforts to provide health education via WeChat. Trial registration ChiCTR1900020736. Registered 15 January 2019.